Family medicine in basic medical education in the 21st century - Pinto, Alexandre De Sousa Martins (2000)
The author delves into the possible evolution of graduate teaching of general/family medicine in the foreseeable future. The issue is debated within the higher education framework. Current and predictable changes in medical practice patterns, the development and growing importance of general/ family medicine, its scientific grounding, the demands from ongoing social developments, and the problems of medical education in general and of teaching general/family medicine, in particular, are all analysed. The general guidelines of the syllabus of the novel Minho University Medical School are briefly mentioned. The author finishes with the hope that teaching clinical skills may once again take up the foremost position it should have in the basic training of 21st century doctors.